2002
DOI: 10.1046/j.1365-2958.2002.02908.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression, mutagenesis and kinetic analysis of recombinant K1E endosialidase to define the site of proteolytic processing and requirements for catalysis

Abstract: Catalytically active, recombinant fusion proteins of bacteriophage E endosialidase were expressed and purified from Escherichia coli. Constructs with different fusion partners added to the amino terminus of the endosialidase were enzymatically active. A post-translational proteolytic cleavage was shown to occur between serine 706 and aspartate 707 to generate the 76 kDa mature enzyme from the 90 kDa translation product. Endosialidase truncated at the C-terminus from aspartate 707 was observed to have the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 57 publications
2
13
1
Order By: Relevance
“…Both K1-dep phage tailspike genes contain an endosialidase, with greater than 96% amino acid sequence identity to the enzyme characterized from the tail of phage 63D (Kataoka et al, 2006; Machida et al, 2000a; Machida et al, 2000b). Both K1-dep(2) and K1-dep(3) (K1E and K1–5, respectively) also have documented endosialidases (Leggate et al, 2002; Leiman et al, 2007; Muhlenhoff et al, 2003). In contrast, sequences of the three K1-ind phages indicate a glycosidase that is most closely related to the coliphage HK620 tailspike.…”
Section: Resultsmentioning
confidence: 99%
“…Both K1-dep phage tailspike genes contain an endosialidase, with greater than 96% amino acid sequence identity to the enzyme characterized from the tail of phage 63D (Kataoka et al, 2006; Machida et al, 2000a; Machida et al, 2000b). Both K1-dep(2) and K1-dep(3) (K1E and K1–5, respectively) also have documented endosialidases (Leggate et al, 2002; Leiman et al, 2007; Muhlenhoff et al, 2003). In contrast, sequences of the three K1-ind phages indicate a glycosidase that is most closely related to the coliphage HK620 tailspike.…”
Section: Resultsmentioning
confidence: 99%
“…The endoE gene open reading frame was amplified by PCR with cloned full-length DNA as a template and ligated into plasmid pQE30 (Qiagen, Ltd., Crawley, United Kingdom) by standard cloning technology to introduce a histidine tag at the N terminus of the recombinant protein; since we have found that the translated gene product undergoes proteolytic cleavage at a site close to the C terminus (15), the location of this tag is critical for subsequent purification of the fusion product. The plasmid was introduced into E. coli BL21(DE3), and the vector was grown in 2xTY broth (16 g of Bacto tryptone, 10 g of yeast extract, and 5 g of NaCl per liter) in controlled batch fermentation culture by using an Electrolab 300 Series Microprocessor-steered 10-liter fermentor with IPTG (isopropyl-␤-D-thiogalactopyranoside) at optical density at 600 nm (OD 600 ) of 0.3 for up to 6 h. Recombinant protein was purified by using immobilized metal (Ni) affinity chromatography of freeze-thawed sonicated bacterial lysates to yield up to 6 mg of His 6 -tagged recombinant endoE/ liter.…”
Section: Methodsmentioning
confidence: 99%
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and immunoblotting indicated a very high purity of product, with no proteins detectable other than the 76-kDa recombinant endoE fusion product. Batches of His 6 -tagged recombinant enzyme were shown to be catalytically active by using the thiobarbiturate assay for release of N-acetylneuraminic acid from K1 polysaccharide extracted from E. coli LP1674 (15,17). There was no loss of enzyme function due to storage of solutions at 4°C for periods of up to 1 year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally endosialidase purification has involved ammonium sulfate precipitation as well as hydrophobic, gel filtration, and DEAE-ion-exchange chromatography [101,104]. More conveniently, endosialidase is produced as a recombinant enzyme as His6-tagged, GST-tagged, and MBP-tagged fusion proteins [14,71,154].…”
Section: Preparation and Properties Of Catalytically Active Endosialimentioning
confidence: 99%